Porosity-Controlled Flow Instability and Vibration Response in Conical Strainers: An Integrated Hydraulic-Structural Evaluation - Akhyan, Amnur; Bin Razali, Mohd Azahari; Hendriko; Mahzan, Shahruddin Bin; Bin Ismail, Iman Fitri (Testing Center for Oil and Gas LEMIGAS, 2025)
Research on how porosity can trigger vibrations due to flow-induced instability (FIV) partially clogged in perforated conical strainer has been conducted integrated experimental. Six conical filters with porosities between 25 and 40 percent, made in straight and staggered perforation patterns, were tested under clean and clogged conditions using a set of tools with a controlled closed-loop flow. Pressure drop, vibration amplitude, and frequency were measured simultaneously to capture the coupled hydraulic-structural response. The results show that the straight configuration with low porosity exhibits strong geometric constriction, which accelerates the formation of the jet flow, increases turbulence intensity, and strengthens the vibration amplitude as blockage increases. Conversely, strainers with a minimum porosity of 30 percent and staggered holes promote more uniform flow distribution, reduce shear layer instability, and result in a more stable frequency response. The effect of pressure drop on vibration confirms that clogged can lead to dynamic instability of the system, particularly in high-risk frequency bands common in piping facilities. These experimental results are highly relevant to oil and gas exploration and exploitation activities during drilling, well testing, and production operations. Where fluctuating flow rates, entrained solids, and increased clogging are unavoidable. These findings provide practical guidance for determining the porosity of conical strainers and the perforation layout to reduce hydraulic losses, mitigate vibration damage, and improve the operational reliability of piping systems in oil and gas facilities.